Ann Roe’s Career Theory and its Implementation in Career Guidance and Counseling - Nuha, Moch. Syihabudin; Alamsyah, Muh. Nur; Muslihati, Muslihati; Zamroni, Zamroni (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2024)
The purpose of this literature study research is to comprehensively find out the basic concepts of Anne Roe's theory, factors that influence career choices, classification of career choices according to Roe, advantages and disadvantages and implementation in career guidance services in schools. The method used is a literature study conducted by collecting, selecting, reading reading sources from literature books, journals, articles as material for analysis to obtain results and conclusions. The results showed that Anne Roe's career choice theory is heavily influenced by Maslow's 8 human hierarchical needs, patterns of acceptance in children, and certain parenting that parents and teachers are not aware of. Because this theory is under the humanistic umbrella and speaks to the influence of parents and children's personalities. It is important for children to be nurtured from an early age as it will affect their career choices in the future.